2022
DOI: 10.3390/brainsci12020161
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Burdens Associated with Huntington’s Disease in Manifest Patients and Care Partners–Comparing to Parkinson’s Disease and the General Population

Abstract: Background: The study provides real-world data on the impact of Huntington’s disease (HD) from the perspective of individuals with HD (IHD) and care partners (HD-CP) and contextualizes these results relative to Parkinson’s disease (PD) and the general population (GP). Methods: Cross-sectional survey of IHD and HD-CP in the US (July 2019–August 2019) conducted using the Rare Patient Voice panel. Data for individuals with Parkinson’s Disease (IPD), the general population (GP), and respective care partners (PD-CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 54 publications
0
21
0
1
Order By: Relevance
“…In the first study Exuzides et al reported data from a large cross-sectional survey in the United States [ 22 ]. The authors reported that individuals with HD had a lower quality of life and more depressive symptoms.…”
mentioning
confidence: 99%
“…In the first study Exuzides et al reported data from a large cross-sectional survey in the United States [ 22 ]. The authors reported that individuals with HD had a lower quality of life and more depressive symptoms.…”
mentioning
confidence: 99%
“…In total, four studies compared the HRQoL of mHDGECs with that of other patient groups or controls [ 21 , 26 , 29 , 42 ]. Two studies included a comparison group of people with other neurological conditions (i.e., cerebellar ataxia, Charcot–Marie–Tooth disease, motor neuron disease, multiple system atrophy, postpolio syndrome, progressive supranuclear palsy [ 29 ] and PD [ 42 ]).…”
Section: Resultsmentioning
confidence: 99%
“…In total, four studies compared the HRQoL of mHDGECs with that of other patient groups or controls [ 21 , 26 , 29 , 42 ]. Two studies included a comparison group of people with other neurological conditions (i.e., cerebellar ataxia, Charcot–Marie–Tooth disease, motor neuron disease, multiple system atrophy, postpolio syndrome, progressive supranuclear palsy [ 29 ] and PD [ 42 ]). In the first study, conclusions were only drawn for the combined sample of neurological conditions, yet the authors stated that the subgroup of mHDGECs ( n = 53) reported significantly higher levels on the HRQoL domains of anxiety and depression compared to all other groups ( n = 213) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HD-Patienten haben im Vergleich zur Allgemeinbevölkerung eine signifikant niedrigere Lebensqualität und eine signifikant höhere Rate an Angststörungen und Depressionen und Suiziden. Auch die pflegenden Angehörigen von HD-Patienten zeigten häufiger Angststörungen und Depressionen als Pflegende in der Allgemeinbevölkerung [21]. In dieser Studie waren die Häufigkeiten von komorbiden Angststörungen (HD-Patienten bzw.…”
Section: Merkeunclassified